Intrinsic and Extrinsic Motivation of Fourth Grade Teachers at Muhammadiyah 1: Motivasi Intrinsik dan Ekstrinsik Guru Kelas IV di Muhammadiyah 1 - Aurellia, Farah; Wardana, Mahardika Darmawan Kusuma (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background: Teacher motivation is a crucial determinant of educational quality, influencing teaching performance, student engagement, and school outcomes. Specific Background: At SD Muhammadiyah 1 Candi, Sidoarjo, understanding the intrinsic and extrinsic motivation of fourth-grade teachers is essential to optimize learning processes. Knowledge Gap: Despite existing studies on teacher motivation, limited research has explored the application of Herzberg’s two-factor theory in the context of Muhammadiyah elementary schools. Aim: This study aims to analyze the intrinsic and extrinsic motivational factors influencing fourth-grade teachers’ teaching performance. Methods: A descriptive qualitative approach was employed, using in-depth interviews, classroom observations, questionnaires, and documentation, with data analyzed through reduction, presentation, and conclusion drawing. Results: Findings indicate that intrinsic motivation—personal satisfaction, teaching enthusiasm, and professionalism—is the primary driver of teacher performance, while extrinsic factors such as salary, social recognition, and work environment serve as reinforcing elements. Novelty: The study highlights the dominant role of intrinsic motivation within a Muhammadiyah school context, emphasizing the interplay between personal dedication and institutional support. Implications: Strengthening intrinsic motivation alongside adequate extrinsic support fosters productive teaching conditions, improving learning quality. Highlights: Intrinsic motivation drives teacher performance. Extrinsic factors reinforce, not lead, motivation. Herzberg’s theory applicable in Muhammadiyah schools. Keywords: Teacher Motivation, Intrinsic Motivation, Extrinsic Motivation, Elementary School, Muhammadiyah